Farm’s Smart BOT - et. al., Dr.S. Geetha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In India, agriculture plays an indispensable role to upgrade the economy. The most important problem prevailing among the Indian farmers is the difficulty of choosing the right crop according to the specific region. This bot provides a complete solution which benefits the farmers to increase their productivity. Various algorithms have been analysed and the best method that suits various purposes are discussed. The proposed bot is platform independent as it supports its functionality in a multi-operating system. This is being implemented using Natural Language Processing (NLP) for text classification and yoloV3 for object detection. The Farm’s Smart BOT provides a complete solution of conversational system along with the integration of various predicting modules like Crop detection, Soil detection, Crop disease detection, suggestions about crop rotation and Weather forecasting.